Developing Managerial Strategies to Foster Energy-Saving Habits in Higher Education Institutions: A Focus on Organizational Culture and Energy Efficiency - Valenzuela, Patricia A.; Salas, Francisco G.; Solares, Efraín; Diaz, Eyran (International Journal of Energy Economics and Policy, 2025)
In the current context of increasing concern for sustainability and energy efficiency, higher education institutions face the challenge of implementing effective managerial strategies that promote energy-saving habits among their employees. This study investigates the relationships between energy- saving attitudes, environmental concern, awareness of energy-saving standards, and institutional energy-saving culture, and how these factors influence employees’ energy-saving habits. Using Structural Equation Modeling (SEM), data from a sample of 165 employees in higher education institutions in northern Mexico were analyzed. The results reveal that attitudes towards energy-saving and knowledge of institutional standards have a significant positive effect on energy-saving habits. Additionally, organizational culture plays a crucial mediating role in the relationship between knowledge of energy-saving standards and energy-saving habits. This study provides valuable insights for policymakers in educational organizations, highlighting the importance of developing an organizational culture that fosters energy efficiency and sustainability. Practical implications include the need for continuous training programs and the implementation of policies that reinforce energy-saving behaviors, thereby contributing to reduced energy consumption and the achievement of institutional sustainability goals.